The evolving role of executive compensation, sustainability performance, and corporate dynamics in the era of corporate sustainability: insights from quantile regression in emerging markets - Ummar Faruk Saeed; Mohammed Abdul-Karim (Cogent Business & Management)
As the global business landscape increasingly prioritizes sustainability, aligning executive compensation with long-term value creation has become a critical challenge, especially in emerging markets. Despite the growing recognition of CEO incentives (CEOI) as a key determinant of firm value (FV), the mechanisms driving this relationship remain underexplored, particularly in the energy sector of the Middle East and North Africa (MENA) region. This study investigates how sustainability performance (SP) mediates and corporate culture (CC) moderates the relationship between CEOI and FV. Leveraging a comprehensive panel dataset of 5,928 firm-year observations, we apply quantile regression to examine the heterogeneous effects of CEOI across different performance levels. To address potential endogeneity, we employ robust estimation techniques, including GMM and IV-2SLS. Our findings reveal a consistently positive relationship between CEOI and FV, with SP serving as a significant mediator particularly at higher performance quantiles. Moreover, CC not only directly enhances FV but also strengthens the effectiveness of CEOI in driving performance across all quantiles. These results enrich the literature on corporate governance by highlighting the synergistic role of executive incentives, sustainability practices, and organizational culture in fostering firm performance.